ZnO based heterojunctions and their application in environmental photocatalysis. (30th August 2016) - Gu, Xiuquan; Li, Cuiyan; Yuan, Shuai; Ma, Mingguo; Qiang, Yinghuai; Zhu, Jiefang
Abstract: As an alternative to TiO2 photocatalysts, ZnO exhibits a large potential for photocatalytic (PC) applications in environmental treatments, such as degradation of wastewater, sterilization of drinking water, and air cleaning. However, the efficiency achieved with ZnO to date is far from that expected for commercialization, due to rapid charge recombination, photo-corrosion as well as poor utilization of solar energy. Fortunately, in recent years, a great number of breakthroughs have been achieved in PC performance (including activity and stability) of micro-/nano- structured ZnO by forming heterojunctions (HJs) with metal nanoparticles (NPs), carbon nanostructures and other semiconductors. In most cases, the improvement of PC performance was ascribed to the better charge separation at the interfaces between ZnO and the other components. Sometimes, the formation of hybrids is also in favor of visible light harvesting. This review summarizes recent advances in the fields of environmental photocatalysis by ZnO based HJs, and especially emphasizes their abilities in degradation of organic pollutants or harmful substances in water. We aim to reveal the mechanism underlying the enhanced PC performance by constructing HJs, and extend the potential of ZnO HJ photocatalysts for future trends, and practical, large-scale applications in environment-related fields.